Determinación del área de la Zona de Reserva Campesina (ZRC) La Montaña Caucana a partir del análisis de variables espaciales (2021)
The purpose of this project was to determine the area for the constitution of the La Montaña Caucana Peasant Reserve Zone (ZRC), through the analysis of spatial variables, allowing the stabilization of the peasant population and territoriality; in addition, to recognize and generate social arrangements on the historical construction of the territory by the Inzaeño, Totoreño and Silviano peasantry. Likewise, with the constitution of the ZRC, it gives the peasant population the opportunity to get involved in the processes of restoration and preservation of strategic natural ecosystems and carry out agricultural activities